(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Climate change, a complex global issue, has prompted a wide range of actors – from nations to tiny communities – to seek solutions to mitigate its consequences. The growing emphasis on collaborative governance has resulted in substantial research on the topic. This paper aims to address the existing research void by using a bibliometric approach to investigate the evolution of studies on collaborative governance in the context of climate change. This study conducted a bibliometric mapping of research on collaborative governance on climate change issues from the first study presented in 2007 to the research conducted in 2023, using 222 articles derived from the Scopus database and Web of Science. Steps for comprehensive bibliometric literature mapping via the VOSviewer software. The study includes a complete overview of significant themes, including the most cited research, contributions from authors, countries, and institutions, as well as network analysis including co-citation, bibliographic coupling, and co-occurrence. Notably, the study looks at which countries have made the most substantial contributions, with the United States dominating with 40 studies over the last decade. The analysis reveals that collaborative governance in climate change, emphasizing its importance as a tool for governments and communities to mitigate climate risks. This is consistent with research emphasizing the need for coordination across multiple players to accomplish effective climate adaptation. The paper focuses on nine diverse research clusters, including community engagement, urban governance, disaster response and economic implications. This study is restricted to bibliometric analysis, which is conducted using sources from the Scopus and Web of Science databases. Future research is required to investigate the use of additional databases that offer a wider range of sources. In the interim, this investigation provides an overview of the concept of Collaborative Governance, which has the potential to serve as a strategy for the adaptation and resilience to climate change in global regions, cities and urban areas. This study conducts a rigorous bibliometric review that improves our theoretical knowledge and practical use of collaborative governance in addressing climate change. It reveals innovative